Preparation method of Sn / C sodium ion battery negative electrode material
By preparing Sn/C composite materials at a temperature below the melting point of tin, the problem of tin loss at high temperatures was solved, and efficient and low-cost preparation of sodium-ion battery negative electrode materials was achieved, thereby improving the cycle stability and electrochemical performance.
Patent Information
- Application Number
- CN202510835763.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-20
- Publication Date
- 2025-10-21
AI Technical Summary
In the existing preparation process of Sn/C sodium-ion battery negative electrode materials, tin loss is easily caused under high temperature conditions, and the cost is high, which affects the cycle stability and consistency.
Tin sulfide is mixed with carbon material at a temperature below the melting point of tin, and the Sn/C composite material is prepared by molten salt electrolysis in an inert atmosphere to ensure that tin is generated on the surface of the carbon material to avoid tin loss, and electrolysis treatment is carried out by contacting the porous sheet with the metal mesh.
The preparation temperature is significantly reduced, the loss of tin is avoided, the cycle stability and electrochemical performance of the material are improved, the cost is low and the operation is simple, and it is suitable for promotion and application.
Smart Images

Figure CN120818863A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a sodium ion battery, and more particularly to a method for preparing a Sn / C sodium ion battery negative electrode material. Background Art
[0002] Driven by the global energy transition and the "dual carbon" goals, the development of new energy storage technologies is crucial for addressing the volatility of renewable energy and achieving green, low-carbon development. While lithium-ion batteries currently dominate the market, increasing shortages, uneven distribution, and rising costs of lithium resources are driving the search for resource-rich, low-cost alternative energy storage technologies. Sodium-ion batteries (SIBs) are one of the most promising next-generation energy storage technologies due to their abundant sodium reserves (2.3% in the Earth's crust, far exceeding lithium's 0.0017%), widespread distribution, and low cost.
[0003] In recent years, sodium-ion batteries have achieved significant breakthroughs in electrode materials, electrolytes, and battery technology. Positive electrode materials have formed three major systems: layered oxides, polyanionic compounds, and Prussian blue. The negative electrode is dominated by hard carbon, supplemented by alloys and transition metal compounds, and the energy density is gradually approaching the level of lithium iron phosphate batteries (120-160 Wh / kg). At the same time, sodium batteries have demonstrated unique advantages in low-temperature performance, fast charging capabilities, and safety, giving them differentiated competitiveness in low-speed electric vehicles, large-scale energy storage, and backup power sources. However, sodium-ion batteries still face challenges such as increasing energy density, optimizing cycle life, and further reducing costs. In particular, the first-cycle efficiency and consistency of the negative electrode material (hard carbon) and the volume expansion problem of the alloy material need to be urgently addressed.
[0004] Tin (Sn) has attracted widespread attention due to its high theoretical capacity (847 mAh / g), but the volume of metallic tin changes greatly during charge and discharge (about 420%), resulting in poor cycle performance. Compounding Sn in the form of nanoparticles with carbon materials to prepare Sn / C composites is a method to improve electrochemical cycle stability. However, currently, the solvothermal method is mainly used to prepare Sn / C composites at higher temperatures (500-900°C) in a protective atmosphere of continuously flowing inert gas. Such high temperature conditions may bring potential dangers and high costs, and the high reaction temperature is prone to Sn (melting point 232 o C) loss. Summary of the Invention
[0005] In order to solve the problem of Sn loss caused by the high reaction temperature in the above-mentioned prior art, the present invention aims to provide a method for preparing Sn / C sodium ion battery negative electrode material, which can realize the preparation of nano-scale Sn / C at a temperature below the melting point of Sn, ensure the cycle stability of the sodium ion battery, and avoid Sn loss during the preparation process. The method is simple, low-cost, and suitable for promotion.
[0006] The preparation method of the Sn / C sodium ion battery negative electrode material of the present invention comprises the following steps: S1, tin sulfide reacts in an aqueous solution containing sodium sulfide to generate sodium thiostannate, which is fully mixed with a carbon material under heating and stirring, and dried to obtain a carbon material with a surface covered with sodium thiostannate; S2, grinding the dried carbon material with a surface covered with sodium thiostannate into powder, and obtaining a porous sheet by tableting; S3, wrapping the porous sheet in a porous metal mesh so that the porous sheet is in full contact with the metal mesh and serves as a cathode, using a graphite rod as an anode and a mixed molten salt of SnCl2-LiCl-KCl as an electrolyte, heating the molten salt electrolyte to 175-225°C under inert atmosphere conditions, and o C, apply a voltage of 1.8-3.0 V, and continue electrolysis for 4-24 h. The tin ions in the sodium thiostannate obtain electrons to generate atomic tin that remains on the surface of the carbon material, obtaining the Sn / C sodium ion battery negative electrode material.
[0007] In a preferred embodiment, in step S1, the carbon material is one of carbon nanotubes, carbon nanofibers, graphite powder, and graphene, and the tin sulfide is SnS2 and / or SnS.
[0008] In a preferred embodiment, in step S1, carbon material, tin sulfide, sodium sulfide and deionized water are added to a beaker, stirred evenly in a magnetic stirrer, the water is evaporated, and then placed at 120 o After drying in a C oven for 24 h, a carbon material with a surface covered with sodium thiostannate was obtained.
[0009] In a preferred embodiment, in step S1 , the mass ratio of the carbon material to tin sulfide is 0.2:1 to 4:1, and the molar ratio of tin sulfide to sodium sulfide is 1:1 to 1:3.
[0010] In a preferred embodiment, in step S1 , the mass ratio of the carbon material to tin sulfide is 0.5:1 to 2:1.
[0011] In a preferred embodiment, in step S1, the magnetic stirring speed is 100-500 r / min, the temperature is 40-80 o C, stirring time is 12-24 h.
[0012] In a preferred embodiment, in step S2, after being ground into powder, tableting is performed at a pressure of 20 MPa and the pressure is maintained for 5 minutes to obtain a porous tablet.
[0013] In a preferred embodiment, in step S2, the powder is ground into powder that can pass through a 150-mesh sieve.
[0014] In a preferred embodiment, in step S3, the molar percentage of SnCl2 in the molten salt electrolyte is 46%-88%.
[0015] In a preferred embodiment, in step S3, the molar percentage of SnCl2 in the molten salt electrolyte is 50%-66%.
[0016] In a preferred embodiment, in step S3, the metal mesh is one of a molybdenum mesh, a copper mesh, a foamed copper, and a foamed nickel.
[0017] In a preferred embodiment, in step S3, the inert atmosphere is argon or nitrogen. In a preferred embodiment, the inert atmosphere is argon or nitrogen with a purity exceeding 99.9%.
[0018] In a preferred embodiment, in step S3, the Sn metal particle size in the Sn / C sodium ion battery negative electrode material is 10-200 nm, and the mass ratio of Sn is 30%-70%.
[0019] In a preferred embodiment, in step S3, the size of Sn metal particles in the Sn / C sodium ion battery negative electrode material is 20-30 nm, and the mass ratio of Sn is 50%-60%.
[0020] In a preferred embodiment, in step S3, the metal mesh is connected to the current collector to form a cathode, the graphite rod is connected to the current collector to form an anode, a graphite crucible or an alumina crucible is used as an electrolytic cell, the cathode and the anode are respectively inserted into the molten salt electrolyte, and after the electrolysis is completed, the cathode is lifted above the molten salt electrolyte, cooled to room temperature and then taken out, and after being taken out, placed in deionized water for ultrasonic treatment, and dried to obtain the Sn / C sodium ion battery negative electrode material.
[0021] In a preferred embodiment, in step S3, the tin ions in the sodium thiostannate gain electrons, generating atomic tin that remains on the carbon material surface. The sulfur anions are then oxidized at the anode to form elemental sulfur. Because the electrolysis reaction temperature is below the melting point of tin, nearly all of the tin in the cathode remains in the carbon, preventing tin loss. Furthermore, because the carbon and sodium thiostannate are evenly mixed, the electrochemical action facilitates the in-situ formation of tin nanostructures.
[0022] In a preferred embodiment, in step S3, the current collector is one of molybdenum wire, nickel wire, and nickel-chromium wire.
[0023] In a preferred embodiment, in step S3, the electrolyte temperature rise rate is 1-3 o C / min, and keep warm for 2-3 hours after heating to the target temperature.
[0024] In a preferred embodiment, in step S3, the electrolyte temperature is 180-200 o C.
[0025] In a preferred embodiment, in step S3, the applied electrolysis voltage is 2.3-2.6 V, and the electrolysis time is 10-16 h.
[0026] The method for preparing the Sn / C sodium-ion battery negative electrode material according to the present invention significantly reduces the operating temperature of the traditional Sn / C preparation process. The operating temperature below the melting point of Sn avoids the loss of Sn. The prepared Sn / C with a nanostructure ensures the cycle stability of the sodium-ion battery. The method is low-cost, simpler to operate, and environmentally friendly. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 is the X-ray powder diffraction spectrum of the Sn / C material prepared in Example 1.
[0028] Figure 2 This is a transmission electron microscope image of the Sn / C material prepared in Example 1.
[0029] Figure 3 This is a sodium storage cycle performance diagram of the Sn / C sodium ion battery negative electrode material prepared in Example 1.
[0030] Figure 4 This is a sodium storage rate performance diagram of the Sn / C sodium ion battery negative electrode material prepared in Example 1. DETAILED DESCRIPTION
[0031] To make the objectives, technical solutions, and advantages of the present invention more clearly understood, the present invention is further described in detail below with reference to the following embodiments. It should be understood that the specific embodiments described herein are intended only to illustrate the present invention and are not intended to limit the present invention.
[0032] Example 1
[0033] Step 1: Mix well.
[0034] Add a certain amount of carbon nanotubes, SnS2, Na2S and deionized water into a beaker to ensure that the mass ratio of carbon nanotubes to tin sulfide is 1:1 and the molar ratio of tin sulfide to sodium sulfide is 1:1. Place the beaker on a magnetic stirrer at 200 r / min and 60 o C for 16 h, and then place at 120 o C oven for 24 h.
[0035] Step 2: Tablet pressing.
[0036] The sample after drying in step 1 was further ground into powder, and then tabletted at a pressure of 20 MPa and maintained at this pressure for 5 minutes to obtain a porous tablet.
[0037] Step 3: Electrolytic treatment.
[0038] Wrap the porous sheet obtained in step 2 in a porous molybdenum mesh so that the porous sheet is in close contact with the metal mesh, then connect the metal mesh and the current collector to form a cathode, and connect the graphite rod and the current collector to form an anode.
[0039] Alumina crucible was used as electrolytic cell, SnCl2-LiCl-KCl mixed molten salt was used as electrolyte, and 2 o The electrolyte was heated to 200 o C and keep warm for 2 h.
[0040] The cathode and anode were inserted into the electrolyte respectively, a voltage of 2.3 V was applied, and electrolysis was continued for 10 h.
[0041] Step 4: Sample processing after electrolysis.
[0042] After the electrolysis is completed, the cathode is lifted above the electrolyte, cooled to room temperature and then taken out. After being taken out, the sample is placed in deionized water for ultrasonic treatment and dried to obtain the Sn / C sodium ion battery negative electrode material.
[0043] The structure and morphology of the sample obtained in Example 1 were characterized by X-ray diffractometer and transmission electron microscope. Figure 1 and 2 .
[0044] Figure 1 The XRD pattern of the sample prepared by the method of Example 1 is shown. o The peak is the characteristic peak of carbon nanotubes, and the other peaks are the characteristic peaks of Sn in Sn / C.
[0045] Figure 2 This figure shows a TEM image of a sample prepared using the method of Example 1. It can be seen that the Sn particles in the Sn / C sample are approximately 20-30 nm in size and are uniformly dispersed. The mass ratio of Sn in the prepared Sn / C sample is approximately 50%.
[0046] In order to verify the electrochemical performance of the prepared Sn / C sodium ion battery anode material, a sodium ion battery anode sheet was prepared using the prepared Sn / C sample as the anode material.
[0047] Figure 3 The cycle curve of the product obtained in this example on a sodium sheet as a half-cell is shown at 100 mA g-1 The first discharge capacity is 481mAh g -1 After 500 cycles, there is still 466 mAh g -1 The capacity retention rate is 97%, showing excellent cycle performance.
[0048] Figure 4 This is the rate performance diagram of the product obtained in this example for a half-cell of sodium sheet, 1A g -1 363 mAhg -1 Capacity, 5A g -1 Still 307 mAh g -1 capacity, showing excellent rate performance.
[0049] Example 2
[0050] This example is basically the same as Example 1, except that in this example, carbon nanotubes are replaced with graphene. The cycle curve of the product obtained in this example on a sodium sheet as a half-cell shows that at 100 mA g -1 The first discharge capacity is 473mAh g -1 After 500 cycles, there is still 446 mAh g -1 The capacity retention rate is 94%, showing excellent cycle performance. When the material is used as the negative electrode of sodium ion battery, it can -1 342 mAhg -1 Capacity, 5A g -1 Still 288mAh g -1 capacity, showing excellent rate performance.
[0051] Example 3
[0052] This embodiment is substantially the same as embodiment 1, except that, in this embodiment, the mass ratio of carbon nanotubes to tin sulfide is 2:1.
[0053] Example 4
[0054] This embodiment is substantially the same as embodiment 1, except that, in this embodiment, the mass ratio of carbon nanotubes to tin sulfide is 0.5:1.
[0055] Example 5
[0056] This embodiment is substantially the same as embodiment 1, except that, in this embodiment, the applied electrolysis voltage is 2.6V.
[0057] Example 6
[0058] This embodiment is substantially the same as embodiment 1, except that, in this embodiment, the electrolysis time is 16 h.
[0059] Example 7
[0060] This embodiment is basically the same as embodiment 1, except that, in this embodiment, the porous sheet is wrapped in nickel foam.
[0061] Example 8
[0062] This embodiment is substantially the same as embodiment 1, except that, in this embodiment, the molar ratio of tin sulfide to sodium sulfide is 1:3.
[0063] Example 9
[0064] This embodiment is basically the same as embodiment 1, except that in this embodiment, the electrolyte temperature is 180 o C.
[0065] Example 10
[0066] This embodiment is basically the same as Example 1, except that, in this embodiment, the molar percentage of SnCl2 in the SnCl2-LiCl-KCl mixed molten salt is 66%.
[0067] Comparative Example 1
[0068] Step 1: Mix well.
[0069] Add a certain amount of SnS2, Na2S and deionized water to the beaker to ensure that the molar ratio of tin sulfide to sodium sulfide is 1:1, and place the beaker on a magnetic stirrer at 200 r / min and 60 o C for 16 h, and then place at 120 o C oven for 24 h.
[0070] Step 2: Tablet pressing.
[0071] The sample after drying in step 1 was further ground into powder, and then tabletted at a pressure of 20 MPa and maintained at this pressure for 5 minutes to obtain a porous tablet.
[0072] Step 3: Electrolytic treatment.
[0073] Wrap the porous sheet obtained in step 2 in a porous molybdenum mesh so that the porous sheet is in close contact with the metal mesh, then connect the metal mesh and the current collector to form a cathode, and connect the graphite rod and the current collector to form an anode.
[0074] Alumina crucible was used as electrolytic cell, SnCl2-LiCl-KCl mixed molten salt was used as electrolyte, and 2 o The electrolyte was heated to 200 o C and keep warm for 2 h.
[0075] The cathode and anode were inserted into the electrolyte respectively, a voltage of 2.3 V was applied, and electrolysis was continued for 10 h.
[0076] Step 4: Sample processing after electrolysis.
[0077] After the electrolysis is completed, the cathode is lifted above the electrolyte, cooled to room temperature and then taken out. After being taken out, the sample is placed in deionized water for ultrasonic treatment and dried to obtain the Sn / C sodium ion battery negative electrode material.
[0078] In order to verify the electrochemical performance of the prepared material, the prepared sample was used as the negative electrode material to prepare the negative electrode sheet of sodium ion battery. -1 The first discharge capacity is 512 mAh g -1 After 500 cycles, it showed 215 mAh g -1 The capacity retention rate is 42%. 1A g -1 391 mAhg -1 Capacity, 5A g -1 214 mAhg -1 capacity.
[0079] Comparative Example 2
[0080] Step 1: Mix well.
[0081] Add a certain amount of graphene, SnS2, Na2S and deionized water into the beaker to ensure that the mass ratio of carbon nanotubes to tin sulfide is 1:1 and the molar ratio of tin sulfide to sodium sulfide is 1:1. Place the beaker on a magnetic stirrer at 200 r / min and 60 o C for 16 h, and then place at 120 o C oven for 24 h.
[0082] Step 2: Tablet pressing.
[0083] The sample after drying in step 1 was further ground into powder, and then tabletted at a pressure of 20 MPa and maintained at this pressure for 5 minutes to obtain a porous tablet.
[0084] Step 3: Soaking.
[0085] The porous sheet obtained in step 2 is wrapped in a porous molybdenum mesh so that the porous sheet is in close contact with the metal mesh.
[0086] The porous molybdenum mesh wrapped with the porous sheet obtained in the above steps was placed in an alumina crucible containing a SnCl2-LiCl-KCl mixed molten salt under an Ar atmosphere at 2 oThe electrolyte was heated to 200 o C and keep warm for 12 h.
[0087] Step 4: Sample processing after soaking.
[0088] After the electrolysis is completed, the cathode is lifted above the electrolyte, cooled to room temperature and then taken out. After being taken out, the sample is placed in deionized water for ultrasonic treatment and dried.
[0089] In order to verify the electrochemical performance of the prepared comparative sample sodium ion battery negative electrode material, a sodium ion battery negative electrode sheet was prepared using the prepared comparative sample as the negative electrode material. The test found that at 100 mA g -1 The first discharge capacity is 142 mAhg -1 , after 500 cycles, only 66 mAh g -1 The capacity retention rate is 46%. -1 85 mAhg -1 Capacity, 5A g -1 Only 47 mAh g -1 capacity.
[0090] Comparative Example 3
[0091] Step 1: Mix well.
[0092] Add a certain amount of carbon nanotubes, SnS2, Na2S and deionized water into a beaker to ensure that the mass ratio of carbon nanotubes to tin sulfide is 1:1 and the molar ratio of tin sulfide to sodium sulfide is 1:1. Place the beaker on a magnetic stirrer at 200 r / min and 60 o C for 16 h, and then place at 120 o C oven for 24 h.
[0093] Step 2: Tablet pressing.
[0094] The sample after drying in step 1 was further ground into powder, and then tabletted at a pressure of 20 MPa and maintained at this pressure for 5 minutes to obtain a porous tablet.
[0095] Step 3: Electrolytic treatment.
[0096] Wrap the porous sheet obtained in step 2 in a porous molybdenum mesh so that the porous sheet is in close contact with the metal mesh, then connect the metal mesh and the current collector to form a cathode, and connect the graphite rod and the current collector to form an anode.
[0097] Alumina crucible was used as electrolytic cell, SnCl2-LiCl-KCl mixed molten salt was used as electrolyte, and 2 o The electrolyte was heated to 250 C / min.o C and keep warm for 2 h.
[0098] The cathode and anode were inserted into the electrolyte respectively, a voltage of 2.3 V was applied, and electrolysis was continued for 10 h.
[0099] Step 4: Sample processing after electrolysis.
[0100] After the electrolysis is completed, the cathode is lifted above the electrolyte, cooled to room temperature and then taken out. After being taken out, the sample is placed in deionized water for ultrasonic treatment and dried to obtain the Sn / C sodium ion battery negative electrode material.
[0101] In order to verify the electrochemical performance of the prepared Sn / C sodium ion battery negative electrode material, a sodium ion battery negative electrode sheet was prepared using the prepared Sn / C sample as the negative electrode material. The cycle curve of the product obtained in this example on the sodium sheet as a half-cell shows that at 100 mA g -1 The first discharge capacity is 178mAh g -1 After 500 cycles, it still has 105 mAh g -1 The capacity retention rate is 59%. The rate performance diagram of the product obtained in this embodiment for sodium sheet half-cell shows that 1A g -1 97mAhg -1 Capacity, 5A g -1 Displayed to have 43 mAh g -1 capacity.
[0102] The test results of Examples 1-2 and Comparative Examples 1-3 are summarized in Table 1 below.
[0103] Table 1 Test results of Examples 1-2 and Comparative Examples 1-3
[0104]
[0105] As can be seen from Table 1, the Sn / C material prepared by the present invention by fully mixing tin sulfide and carbon material and then performing molten salt electrolysis at a relatively low temperature has excellent sodium storage characteristics and cycle performance. Specifically, at 100 mAg -1 At a current density of 1.5 GHz, the first discharge capacity is between 400 and 500 mAh g -1 After 500 charge and discharge cycles, the capacity retention rate of the material is between 90% and 99%, indicating that the material can still maintain a high sodium storage performance after multiple cycles; at 5A g -1 At high current density, the specific capacity of the material is 250-350 mAh g -1 The results show that even at higher charge and discharge rates, the material can still maintain a high sodium storage capacity, demonstrating its excellent rate performance.
[0106] The above description of the embodiments is intended to facilitate understanding and use of the invention by those skilled in the art. It will be apparent that those skilled in the art can readily make various modifications to these embodiments and apply the general principles described herein to other embodiments without requiring inventive effort. Therefore, the present invention is not limited to the above-described embodiments. Improvements and modifications made by those skilled in the art based on the disclosure of the present invention, without departing from the scope of the present invention, should be within the scope of protection of the present invention.
Claims
1. A method for preparing a Sn / C sodium ion battery negative electrode material, characterized in that: The preparation method comprises the following steps: S1, tin sulfide reacts in an aqueous solution containing sodium sulfide to form sodium thiostannate, which is then thoroughly mixed with the carbon material under heating and stirring, and dried to obtain a carbon material having a surface covered with sodium thiostannate; S2, grinding the dried carbon material with the surface covered with sodium thiostannate into powder, and obtaining a porous sheet by tableting; S3, the porous sheet is wrapped in a porous metal mesh so that the porous sheet and the metal mesh are in full contact and used as a cathode, the graphite rod is used as an anode, and the mixed molten salt of SnCl2-LiCl-KCl is used as an electrolyte. Under inert atmosphere, the molten salt electrolyte is heated to 175-225 o C, apply a voltage of 1.8-3.0 V, and continue electrolysis for 4-24 h. The tin ions in the sodium thiostannate obtain electrons to generate atomic tin that remains on the surface of the carbon material, obtaining the Sn / C sodium ion battery negative electrode material.
2. The preparation method according to claim 1, characterized in that The carbon material is one of carbon nanotubes, carbon nanofibers, graphite powder, and graphene, and the tin sulfide is SnS2 and / or SnS.
3. The preparation method according to claim 1, characterized in that The mass ratio of the carbon material to tin sulfide is 0.2:1 to 4:1, and the molar ratio of tin sulfide to sodium sulfide is 1:1 to 1:
3.
4. The preparation method according to claim 1, characterized in that The molar percentage of SnCl2 in the molten salt electrolyte is 46%-88%.
5. The preparation method according to claim 1, characterized in that The metal mesh is one of molybdenum mesh, copper mesh, foam copper and foam nickel.
6. The preparation method according to claim 1, characterized in that The inert atmosphere is argon or nitrogen.
7. The preparation method according to claim 1, characterized in that The Sn metal particle size in the Sn / C sodium ion battery negative electrode material is 10-200 nm, and the mass ratio of Sn is 30%-70%.
8. The preparation method according to claim 1, characterized in that In step S3, the metal mesh is connected to the current collector to form a cathode, the graphite rod is connected to the current collector to form an anode, a graphite crucible or an alumina crucible is used as an electrolytic cell, the cathode and the anode are respectively inserted into the molten salt electrolyte, and after the electrolysis is completed, the cathode is lifted above the molten salt electrolyte, cooled to room temperature and then taken out, and then placed in deionized water for ultrasonic treatment, and dried to obtain the Sn / C sodium ion battery negative electrode material.
9. The preparation method according to claim 8, characterized in that The current collector is one of molybdenum wire, nickel wire and nickel-chromium wire.
10. The preparation method according to claim 1, characterized in that In step S3, the electrolyte temperature rise rate is 1-3 o C / min, and keep warm for 2-3 hours after heating to the target temperature.
